Analgesic effect of photobiomodulation after placement of elastomeric separators: randomized controlled clinical trial - Ortega, Silvana Machado (2022)
Objective: Pain resulting from the positioning of elastomeric separators is a strong reason for abandoning orthodontic treatment. So, this study aims to verify the analgesic effects of photobiomodulation (PBM) in participants submitted to orthodontics with elastomeric separators. Methods: Participants were individuals who received separators on the mesial and distal surfaces of the first molars. They were randomly separated into two groups: an experimental group that received photobiomodulation (PBM) (n=22) and a placebo group (n=22). After the positioning of the separators, the PBM group received one application of PBM (2 J of energy applied in 20 seconds per point, adding up to 12 J per molar (6 J on the vestibular surface and 6 J on the lingual surface) over the cervical portion and the apical third of the tooth. Pain was measured one hour after placement, with the aid of a visual analog scale (VAS). Statistical analysis involved the Mann-Whitney, Fisher’s Exact and chi-square tests. Results: Reports of severe pain only occurred in the placebo group. However, a larger percentage of the individuals in the PBM group reported feeling moderate pain compared to this same intensity in the placebo group. No significant differences among groups were found with regards to reports of mild pain and no pain. An association was found between pain and the female sex in both groups. Conclusion: Significant difference was found in severe pain sensitivity when PBM was applied after the positioning of elastomeric separators, favoring the irradiated participants. Thus, PBM may be a useful tool in orthodontic treatment. Clinical Trials Reference Number (www.ClinicalTrials.gov), NCT03939988.